How Moving to Quebec Has Affected My Theology - Baum, Gregory (Toronto Journal of Theology, 2010)
In this lecture given at the 2009 meeting of the American Academy of Religion in Montreal, Gregory Baum reports how moving to Quebec has affected his practical theology. He mentions three issues of great importance to this French-speaking society that demanded new ethical reflection on his part: the character of an ethically acceptable nationalism, the appropriate response to the cultural weight of English in North America, and an acceptable alternative to Canadian multiculturalism. Thanks to the Montreal-based Karl Polanyi Institute, Baum discovered Karl Polanyi's socio-economic thought critical of the unregulated market system, that differs from Marxism, attends to cultural and ethical issues, and reveals a certain affinity with Catholic social teaching. Polanyi offers a theoretical foundation for the social economy and community efforts to reform society from the bottom up.
Religion Studies
Keywords: American Academy of Religion - Congresses; BAUM; Gregory; Montreal; Polanyi institute; Quebec; bilingualism; conferences & conventions; congresses; inter-culturalism; nationalism; religious life; religious studies

Social Economy and the fight against Social Exclusion: Preliminary remarks with reference to the Greek welfare state - Adam, Sofia (2010)
Recent academic discourse and European social policies highlight the (potential) effectiveness of social economy practices as a means to address social exclusion especially for the more disadvantaged social groups. Apart from terminological debates on the aforementioned troubled concepts, fundamental questions needs to be examined: To what extent social economy practices flourish as a result of policy shifts towards further commercialization of public social services or to what extent do they emerge from bottom up collective survival strategies? This paper attempts to address this question with reference to the political economy of the Greek welfare state.
Keywords: Greece; economic sociology; embeddness; political economy; social economy; substantive approach; welfare state